Circulating Interferon Production in the Mouse : Origin and nature of cells involved and influence of animal genotype - De Maeyer, Edward (The Rockefeller University Press, 1970)
A radiobiological study of circulating interferon production in the mouse was undertaken in the hope of elucidating the site(s) of circulating interferon production. After total body X-irradiation of the animals, different radiosensitivities of circulating interferon production were observed with different viral inducers. Myxovirus-induced circulating interferon production was especially radiosensitive. Moreover, a study of interferon production in syngeneic and xenogeneic radiochimeras demonstrated that cells producing NDV (Newcastle disease virus)-induced circulating interferon were derived from hematopoietic stem cells. In addition, treatment of mice with antilymphocyte serum significantly reduced NDV- and Sendai virus-induced circulating interferon, as opposed to other inducers. Taken together, these results strongly suggest that the lymphocyte is the major source of myxovirus-induced circulating interferon. A survey of interferon production in 12 inbred mouse strains, using NDV as inducer, revealed the existence of low and high producers. A Mendelian analysis carried out with low producing Balb/c and high producing C57BL indicated that the difference between low and high interferon producers was caused by a single, autosomal, codominant factor.